Effect of learning on the change of the ball velocity of the set shot in the team handball - Pori, P.; Skaza, V.; Bon, M.; Sibila, M.; Stirn, I. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The primary purpose of this study was to analyze the effect of learning on the change of the ball velocity of the set shot (shot from the ground) in the Team handball. We found out that the learning process significantly affects the rate of ejection of the ball of analyzed shots by the female students as well as male students. We demonstrated that even relatively short transformative process of learning motor skills in handball, provides positive effects on quality of set shot performance in the Team handball.